2018
DOI: 10.20533/ijtie.2047.0533.2018.0153
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Learning Modules to Enhance Study Skills

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The learning product developed by the researcher on the macromedia flash module is considered suitable because the level of validity of the two validators has a strong relevance with this validity coefficient of more than 75% with the level of practicality after being given a limited trial to students getting a very practical category with an average score of 3.32 % and the effectiveness of the macromedia flash module could be seen in field trials on students through pre-test and post-test with an average score of 56.00% during the pre-test and 89.20% during the post-test so that the macromedia flash module can help lecturers and students to make the lecture process more effective. These results are in accordance with the results of previous studies which also applied modules in presenting various materials (Cramer, Ross, Plant, & Pschibul, 2018;Septia, Edrawati, & Pratiwi, 2016;Supriharyanti, Usodo, & Slamet, 2020).…”
Section: ) Effectiveness Of Macromedia Flashsupporting
confidence: 92%
“…The learning product developed by the researcher on the macromedia flash module is considered suitable because the level of validity of the two validators has a strong relevance with this validity coefficient of more than 75% with the level of practicality after being given a limited trial to students getting a very practical category with an average score of 3.32 % and the effectiveness of the macromedia flash module could be seen in field trials on students through pre-test and post-test with an average score of 56.00% during the pre-test and 89.20% during the post-test so that the macromedia flash module can help lecturers and students to make the lecture process more effective. These results are in accordance with the results of previous studies which also applied modules in presenting various materials (Cramer, Ross, Plant, & Pschibul, 2018;Septia, Edrawati, & Pratiwi, 2016;Supriharyanti, Usodo, & Slamet, 2020).…”
Section: ) Effectiveness Of Macromedia Flashsupporting
confidence: 92%
“…Usmeldi (2018) found that research-based learning modules with Predict Observe-Explain strategies can improve students' competence in Physics. Cramer et al (2018) found that students who received learning modules before or after a midterm improved their performance on the midterm and final exams. Students who completed the modules indicated they enjoyed them, scoring significantly higher on their final examination.…”
Section: Teachers' Evaluation Of the Ilpmentioning
confidence: 95%
“…Thus, business environment scanning is necessary at every point in time even when uncertainties are not expected (Nini, 2020). However, it has been established that employee skill update is a strategy for organisational resilience, competitiveness, growth and sustainability (Cramer et al, 2018). It is against this premise the first proposition is hypothesized.…”
Section: Upskilling (Us) and Situation Awareness (Sa)mentioning
confidence: 99%